Drought characteristics and their impact on vegetation net primary productivity in the climate-sensitive transition zones of North China - Xueying Zhang; Bo Zhang; Xiao Hou; Di An; Zhexi Wu (PLoS ONE, 2026)
Net Primary Productivity (NPP) serves as a key measure of ecosystem production capacity and carbon absorption ability. Evaluating the arid characteristics and their NPP impact in the climate-sensitive transition zones of North China (North China’s humid and semi-humid warm temperate regions) is vital for studying regional climate change, improving ecosystem adaptation, and promoting sustainable development. We analyze drought characteristics at multiple temporal scales (2001−2020) using the Standardized Potential Evapotranspiration Index (SPEI) and Standardized Soil Moisture Index (SSMI). The Carnegie-Ames-Stanford approach (CASA) model was employed to simulate and estimate NPP values, quantify NPP dynamics, and assess vegetation productivity responses to drought stress. We found that droughts showed a slight easing trend from 2001 to 2020. Over the long term, drought intensity and extent were relatively minor. Over the short term, there were frequent occurrences of short-duration, high-intensity droughts. Overall, NPP showed an upward trend, with a decreasing spatial distribution from the central and north-central regions toward the east and west. The fastest average annual growth rate was observed in grassland NPP (8.02g C·m -2 a -1 ), followed by woodland (4.03g C·m -2 a -1 ). Precipitation is an important factor that affects vegetation NPP. Areas with a high correlation between NPP and SPEI-12 are primarily grasslands. Significant relationships exist between NPP and seasonal SPEI-3: positive in summer and negative in winter. Grasslands are most sensitive to drought; forests, on the other hand, exhibit drought resistance and a delayed response to such conditions.